Assessment of influence of silane modified zirconia nanoparticle content on weather resistance of water-borne acrylic coating - Nguyen Thuy Chinh,; Dao Phi Hung,; Nguyen Xuan Thai,; Nguyen Anh Hiep,; Thai Hoang, (Vietnam Journal of Science and Technology, 2023)
Water-borne acrylic resin has attracted much attention thanks to its environmetally  friendly, high weather stability, good mechanical properties, high toughness. It is widely used in coatings, ships, bridges, locomotives, etc. In this work, the effect of ZrO2 nanoparticles content which were modified with (3-glycidyloxypropyl)triethoxysilane (GPTS) on the weather resistance of the acrylic emulsion coatings was tested and discussed. The change in functional groups, carbonyl index value, gloss, weight and morphology of the coatings before and after accelerated weathering test was investigated. The obtained results showed that the GPTS modified ZrO2 nanoparticle content had a significant effect on the characteristics of acrylic emulsion coatings. The 2 wt.% content of GPTS modified ZrO2 nanoparticles exhibited a highest efficiency in improvement of weather resistance of acrylic emulsion coatings. This result indicated that acrylic emulsion coating filled by the GPTS modified ZrO2 nanoparticles is potential for outdoor applications.